Male partner involvements in PMTCT: a cross sectional study, Mekelle, Northern Ethiopia - Haile, Fisaha (BioMed Central, 2014)
BACKGROUND: Male partner participation is a crucial component to optimize antenatal care/prevention of mother to child transmission of HIV(ANC/PMTCT) service. It creates an opportunity to capture pregnant mothers and their male partners to reverse the transmission of HIV during pregnancy, labour and breast feeding. Thus involving male partners during HIV screening of pregnant mothers at ANC is key in the fight against mother to child transmission of HIV(MTCT). So, the aim of this study is to determine the level of male partner involvement in PMTCT and factors that affecting it. METHODS: A Cross-sectional study was conducted among 473 pregnant mothers attending ANC/PMTCT in Mekelle town health facilities in January 2011. Systematic sampling was used to select pregnant mothers attending ANC/PMTCT service after determination of the client load at each health facility. Clinic exit structured interviews were used to collect the data. Finally multiple logistic regression was used to identify factors that affect male involvement in ANC/PMTCT. RESULTS: Twenty percent of pregnant mothers have been accompanied by their male partner to the ANC/PMTCT service. Knowledge of HIV sero status [Adj.OR (95% CI) = 0.43 (0.18- 0.66)], maternal willingness to inform their husband about the availability of voluntary counselling and testing services in ANC/PMTCT [Adj.OR (95% CI) =3.74(1.38-10.17)] and previous history of couple counselling [Adj.OR (95% CI) =4.68 (2.32-9.44)] were found to be the independent predictors of male involvement in ANC/PMTCT service. CONCLUSION: Male partner involvement in ANC/PMTCT is low. Thus, comprehensive strategy should be put in place to sensitize and advocate the importance of male partner involvement in ANC/PMTCT in order to reach out male partners.